Α‐Triazolylboronic Acids: A Promising Scaffold for Effective Inhibitors of KPCs. (22nd June 2020) - Introvigne, Maria Luisa; Taracila, Magdalena A.; Prati, Fabio; Caselli, Emilia; Bonomo, Robert A.
Abstract: Boronic acids are known reversible covalent inhibitors of serine β‐lactamases. The selectivity and high potency of specific boronates bearing an amide side chain that mimics the β‐lactam's amide side chain have been advanced in several studies. Herein, we describe a new class of boronic acids in which the amide group is replaced by a bioisostere triazole. The boronic acids were obtained in a two‐step synthesis that relies on the solid and versatile copper‐catalyzed azide–alkyne cycloaddition (CuAAC) followed by boronate deprotection. All of the compounds show very good inhibition of the Klebsiella pneumoniae carbapenemase KPC‐2, with K i values ranging from 1 nM to 1 μM, and most of them are able to restore cefepime activity against K. pneumoniae harboring bla KPC‐2 . In particular, compound 1 e, bearing a sulfonamide substituted by a thiophene ring, proved to be an excellent KPC‐2 inhibitor ( K i =30 nM); it restored cefepime susceptibility in KPC‐Kpn cells (MIC=0.5 μg/mL) with values similar to that of vaborbactam ( K i =20 nM, MIC in KPC‐Kpn 0.5 μg/mL). Our findings suggest that α‐triazolylboronates might represent an effective scaffold for the treatment of KPC‐mediated infections. Abstract : Fighting K. pneumoniae carbapenemases : The enzymatic activity and ability to restore cefepime susceptibility of 1, 2, 3‐triazol‐1‐ylmethaneboronic acids has been investigated. Comparing them with known inhibitors such as avibactam and vaborbactam provides some insights into their docking. Compound 1 g with a p ‐cyanophenyl‐sulfonamide substituent shows the best K i (1 nM), but a thiophene ring (1 e ) decreases the MIC to 0.5 μg/mL.